Navigating digital transformation: Insights from recent studies on process automation and innovation (International Seven Journal of Multidisciplinary, 2024)
The integration of process automation and digital transformation is reshaping modern business practices, driving efficiency, innovation, and strategic agility. Studies reviewed provide comprehensive insights into how technologies such as Artificial Intelligence (AI), Robotic Process Automation (RPA), and the Internet of Things (IoT) are revolutionizing various sectors, particularly manufacturing and process industries. Research by Bichel et al. (2023) explores how AI and RPA are transforming workplaces, emphasizing the need for businesses to adapt to rapidly changing environments and promote employee creativity. Their study highlights the importance of establishing intelligent IT ecosystems and integrating new strategies across departments to leverage digital transformation effectively. Sjödin et al. (2018) focus on the development of "smart factories," which use advanced digital technologies to enhance operational efficiency, product quality, and sustainability. They identify the benefits of smart factories, including reduced costs and increased adaptability, while also noting the significant challenges of implementing such large-scale transformations. Their proposed maturity model emphasizes the need for cultivating digital skills, adopting agile processes, and using modular technologies. Chirumalla (2021) investigates how digitalization and Industry 4.0 technologies can improve process industries by enhancing product quality and operational flexibility. The study develops a framework with 19 dynamic capabilities for transitioning from traditional to digitally-enabled process innovations, identifying key challenges and enablers for successful implementation. Malik et al. (2021) examine the broad application of digital transformation across engineering domains, highlighting its role in automating traditional processes and addressing big-data challenges. The editorial presents 52 applications of digital transformation, showcasing advancements in areas such as cybersecurity, intelligent manufacturing, and advanced construction.